Effect of Mahuang Fuzi and Shenzhuo Decoction on Idiopathic Membranous Nephropathy: A Multicenter, Nonrandomized, Single-Arm Clinical Trial - Dong, Zhaocheng; Dai, Haoran; Gao, Yu; Jiang, Hanxue; Liu, Meiqi; Liu, Fei; Liu, Wenbin; Feng, Zhendong; Zhang, Xiaoyan; Ren, Aijie; Li, Xiaolan; Rui, Hongliang; et al. (Frontiers in Pharmacology, 2021)
Objective: To explore the clinical effect of Mahuang Fuzi and Shenzhuo Decoction on idiopathic membranous nephropathy. Methods: This study is a multicenter, nonrandomized, single-arm clinical trial carried out as per the objective performance criteria, with the target being set at 35.0%. 184 cases of patients suffering from idiopathic membranous nephropathy with Shaoyin Taiyin syndrome were collected. These patients were treated with Mahuang Fuzi and Shenzhuo Decoction with a follow-up period of 3 years. The 24-hour urine protein and blood albumin were observed, and the remission rates of the patients were compared with the target. Results: The mean follow-up time was 18 (12.5, 30) months, and the remission rate was 61.4%, which is a statistically significant difference from the target group of 35%. The remission rates for patients who had and had not used immunosuppressive therapy were 59.6 and 65.5%, respectively, but the difference was not statistically significant (p = 0.254). However, the albumin before the treatment and the course of treatment of the patients was significantly correlated with the disease remission (p < 0.05). However, the albumin before the treatment and the course of treatment of the patients was significantly correlated with the disease remission (p < 0.05). There were no significant changes in renal function before and after treatment, and no severe adverse events occurred during treatment. Conclusion: Mahuang Fuzi and Shenzhuo Decoction have significant effects on idiopathic membranous nephropathy, and has the same effect on patients with membranous nephropathy who are newly treated as well as those who have been treated with immunosuppressive therapy without remission. In addition, the efficacy of this regimen is related to the albumin and the duration of the therapy, but not to 24-hour urine protein or other factors.